Self-assembled coordination thioether silver(I) macrocyclic complexes for homogeneous catalysis - Cao, Zhen; Lacoudre, Aline; Rossy, Cybille; Bibal, Brigitte (Beilstein Journal of Organic Chemistry, 2019)
The bis-ortho-thioether 9,10-bis[(o-methylthio)phenyl]anthracene was synthesized as a syn-atropisomer, as revealed by X-ray diffraction. This alkylaryl thioether ligand (L) formed different macrocyclic complexes by coordination with silver(I) salts depending on the nature of the anion: M2L2 for AgOTf and AgOTFA, M6L4 for AgNO3. A discrete M2L complex was obtained in the presence of bulky PPh3AgOTf. These silver(I) complexes adopted similar structures in solution and in the solid state. As each sulfur atom in the ligand is prochiral, macrocycles L2M2 were obtained as mixtures of diastereoisomers, depending on the configurations of the sulfur atoms coordinated to silver cations. The X-ray structures of the two L2·(AgOTf)2 stereoisomers highlighted their different geometry. The catalytic activity of all silver(I) complexes was effective under homogeneous conditions in two tandem addition/cycloisomerization of alkynes using 0.5–1 mol % of catalytic loading.
Keywords: coordination macrocycle; homogeneous catalysis; prochiral; silver complex; thioether ligand